Analysis of corporate governance and corporate performance in the 2007-2008 financial crisis - Tan, Kean Bu (2010)
Alan Greenspan described the recent financial crisis as a “once-in-a-century credit tsunami”, born of a collapse deep inside the US housing sector. This phrase caught our attention and we immediately took an interest to find out the main cause of this crisis that the whole world is embroiled in. We believe that that there must be a fundamental cause that contributed significantly to the global financial crisis. This factor may actually be associated with corporate governance, an issue of growing importance, both theoretically and practically. Hence, the objective of our study is to empirically identify the relationship of corporate governance and corporate performance in the recent 2007 financial crisis, using data of 67 financial firms in the S&P 500 that were involved in the crisis with varying severities. We will be addressing on one key dimension of corporate governance – ownership concentration. As for the corporate performance measure, cumulative abnormal returns (CAR) and Tobin q are used. We will first analyse the relationship between corporate governance and corporate performance before and during the financial crisis, using a simple linear regression on various governance index group dummies. The measure of performance is each firm’s cumulative abnormal returns (CAR) before and during the crisis, and the governance index is obtained from WRDS and BoardAnalyst.